Tiling by squares, Kirchhoff’s laws and a flow problem in the economy - Maciuk, Arkadiusz; Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The problem of tiling by squares was formulated more than one hundred years ago and has been mostly regarded as an interesting mathematical issue in geometry, yet without any special practical associations. In addition to a historical outline of the problem, this paper demonstrates how Smith’s 1940 method using digraphs helps associate an issue linked to two-dimensional dissection or packaging with such economic problems as transportation network planning, researching linkages between suppliers and the like. We also discuss simple perfect squared rectangles whose relevant laws of nature are as yet unknown, according to the principle that elegant scientific structures sooner or later find their equivalents in the real world
Didactics of Mathematics, 2017, Nr 14 (18), s. 33-44
Keywords: squarings; digraph; Kirchhoff’s laws; flow problem in the economy